Assessment and treatment of elopement maintained by chase. (19th July 2020) - Blowers, Andrew P.; Rodriguez, Nicole M.; Cohrs, Victoria L.; Luczynski, Kevin C.; Aragon, Michael
Abstract: Elopement can have serious or fatal consequences associated with leaving the presence of an adult or getting lost (e.g., traffic injury and drowning). Given the dangers associated with elopement, caregivers are likely to chase after their child when elopement occurs. Like other forms of attention that follow problem behavior, chasing and retrieving the child may serve as a reinforcer and therefore maintain elopement. However, no study to date has evaluated whether elopement is sensitive to positive reinforcement in the form of chase. We evaluated the effects of chase on elopement with an 8‐year old boy diagnosed with autism. Elopement was maintained, at least in part, by chase. We then conducted a treatment evaluation in which we tested the effects of various antecedent‐ and consequence‐based treatment components within a multiple schedule.